Human Capital and the Dynamic Effects of Trade - Raphael A. Auer (Swiss National Bank, Study Center Gerzensee, 2015)
This paper examines the cross-country income and welfare consequences of trade-induced human capital (dis-)accumulation. The model is based on heterogeneous workers who make educational decisions in the presence of complete markets. When such heterogeneous workers invest in schooling, high type agents earn a surplus from their investment. In the presence of cross-country differences in skill-augmenting technology, trade shifts this surplus to rich countries that can use skills more efficiently. Thus, while the static gains from trade may lead to convergence, the dynamic gains from trade occur to initially rich countries, thus leading to cross-country divergence of income and welfare. The second part of the paper endogenizes world prices, documenting that as trade liberalization concentrates skills in countries with a high level of skill augmenting technology, it thereby increases the effective global supply of skilled labor. Despite the resulting decline in the price of skill-intensive goods, trade is shown to be skill-biased.
Keywords: F11; F14; F16; 330; Factor Content of Trade; Employment; Human Capital; Economic Growth